Radicalisation model: learning from Malaysian militant-extremists - Muhammad Uthman El-Muhammady, Ahmad El-Muhammady (Routledge, 2020)
In facing the threat of terrorism, a holistic counter-terrorism strategy is needed. In a practical sense, holistic counter-terrorism strategy means the application of holistic approaches combining the use of hard and soft approaches with the main focus to eliminate the terrorist organisation and to defeat the extremist ideology in its potential or actual forms. Some countries employ the hard approach – the use of military capabilities – in defeating terrorism. Admittedly, it is capable of destroying the terrorist organisations. But, the ideology remains intact. Afghanistan and Iraq are the best case in point. The growing insurgencies in Afghanistan and Iraq after the occupation of coalition forces in 2001 and 2003 proved that the use of kinetic forces has limited effect in combating terrorism. Their failure to stem the rise of insurgencies after the occupation led many people to realise that another strategy is needed. The application of soft approaches such as deradicalisation and countering/preventing violent extremism (CPVE) programme which aim at tackling the ideological roots of terrorism is considered one of the most effective strategies in dealing with the problem. Southeast Asia, Malaysia, Singapore and Indonesia are known to have adopted this approach besides Saudi Arabia, Yemen, Jordan just to name a few. However, it is important to emphasise that an effective deradicalisation programme is contingent upon our understanding of radicalisation. An accurate diagnosis of radicalisation phenomena is a critical factor in achieving successful terrorist rehabilitation/deradicalisation, because individual radicalisation is unique in nature. It varies according to individual, gender, group and socio-political context. Radicalisation is not a ‘fit-for-all’ phenomena. In fact, there are multiple pathways and processes to individual radicalisation. Thus, based on the above imperatives, the chapter seeks to explore and advance a conceptual model of radicalisation drawn on the experience of militant–extremists in Malaysia. In doing so, this chapter is divided into five sections. The first section deals with a brief historical background and context in which the model is developed. The second section provides some surveys on the theoretical explanation of radicalisation. The third section explores and proposes the radicalisation model based on the experience of militant–extremists in Malaysia. The fourth section highlights the essential elements contributing to radicalisation in Malaysia, and the fifth section discusses the nature and success of Malaysia’s rehabilitation programme.